2016
DOI: 10.1590/2317-4889201620160006
|View full text |Cite
|
Sign up to set email alerts
|

Textural patterns, mineralogy, and chemistry of sandstone-related Calçadinha chalcedony (Piauí, Brazil)

Abstract: Paleozoic sandstones of the Parnaíba Basin, in addition to hosting opal deposits, also have occurrences of chalcedonies with potential for mineral and ornamental handicrafts, in addition to assisting the understanding of the geological evolution of the basin. However, the chalcedonies were not investigated yet, and this study intended to fulfill this gap by the investigation of the chalcedonies of Calçadinha in Piauí. Fieldwork, microtexturals analysis, X-ray diffraction and scanning electron microscopy with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…6) [1,5], which gives agate stone is a distinctive brown or red color, and is sometimes in the form of successive lines with different concentrations of this element. Several researchers have suggested that agate bands form as a result of crystallization from hot aqueous fluids [15]. The combination of elements such as Al, Fe and Mn observed in the jaspar samples (Fig.…”
Section: Micro-mineralogical Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…6) [1,5], which gives agate stone is a distinctive brown or red color, and is sometimes in the form of successive lines with different concentrations of this element. Several researchers have suggested that agate bands form as a result of crystallization from hot aqueous fluids [15]. The combination of elements such as Al, Fe and Mn observed in the jaspar samples (Fig.…”
Section: Micro-mineralogical Analysismentioning
confidence: 90%
“…The precise mineral analysis of selected samples of agate species showed that the main mineral component in them is quartz (Fig. 4,5) [14], and it is believed that it is the main phase in these minerals, as no other phases may be associated with it, such as terdymite or cristobalite [15]. Microscopic study and electron microscopy SEM images of the studied agate by examining the geomorphology of the surface grains.…”
Section: Micro-mineralogical Analysismentioning
confidence: 99%